Implementation of Trait and Factor Career Counseling Services for Students' Career Readiness at SMK Negeri 1 Palopo - Jimmy Jimmy; Nur Saqinah Galugu; Septya Suarja (Indonesian Journal of Guidance and Counseling: Theory and Application, 2024)
Career readiness is crucial for students in determining their career decisions after completing their studies, especially at the vocational school level. This research aims to investigate the influence of implementing Trait and Factor Career Counseling Services to enhance students' career readiness at SMK Negeri 1 Palopo. The population for this study consisted of 85 students from the second grade of TKJ department, and through a pre-test, 9 students were identified with very low to low career readiness. This study used a pre-experimental research design with a one-group pretest-post-test approach. It began with a pre-test which was conducted through questionnaire distribution, followed by the provision of career counseling services, and concluded with a post-test. Data was collected using a scale measuring career readiness, validated and confirmed for reliability through product moment correlation and Cronbach's Alpha. Career counseling services were administered to the sample, and the results show a significant improvement in career readiness post-intervention, supported by paired sample statistics and hypothesis testing using SPSS. These findings indicate that Trait and Factor-based career counseling positively influences students' career readiness. Kesiapan karir sangat penting bagi siswa dalam menentukan keputusan karirnya setelah menyelesaikan studinya, khususnya pada jenjang sekolah kejuruan. Penelitian ini bertujuan untuk mengetahui pengaruh penerapan Layanan Konseling Sifat dan Faktor Karir terhadap peningkatan kesiapan karir siswa di SMK Negeri 1 Palopo. Populasi penelitian ini terdiri dari 85 siswa kelas II Jurusan TKJ, dan melalui pre-test diketahui 9 siswa memiliki kesiapan karir sangat rendah hingga rendah. Penelitian ini menggunakan desain penelitian pre-eksperimental dengan pendekatan one-group pretest-post-test. Diawali dengan pre-test yang dilakukan melalui pembagian kuesioner, dilanjutkan dengan pemberian layanan konseling karir, dan diakhiri dengan post-test. Data dikumpulkan dengan menggunakan skala pengukuran kesiapan karir, divalidasi dan dikonfirmasi reliabilitasnya melalui korelasi product moment dan Cronbach's Alpha. Layanan konseling karir diberikan kepada sampel, dan hasilnya menunjukkan peningkatan kesiapan karir yang signifikan pasca intervensi, didukung dengan statistik sampel berpasangan dan uji hipotesis menggunakan SPSS. Temuan ini menunjukkan bahwa konseling karir berbasis Sifat dan Faktor berpengaruh positif terhadap kesiapan karir siswa.